Aminopropyl Functionalised MCM-41: Synthesis and Application for Adsorption of Pb(II) and Cd(II) - Pham Dinh Du; Nguyen Trung Hieu; Thuy Chau To; Long Giang Bach; Mai Xuan Tinh; Tran Xuan Mau; Dinh Quang Khieu (Advances in Materials Science and Engineering)
This paper shows a comparison of porous properties of aminopropyl-MCM-41 materials functionalised via the direct and indirect methods. The obtained materials were characterised using X-ray powder diffraction (XRD), transmission electron microscopy (TEM), thermogravimetric analysis-differential scanning calorimeter (TGA-DSC), adsorption/desorption isotherms of nitrogen, and Fourier-transfer infrared (FT-IR) spectroscopy. The results showed that the direct method provided the aminopropyl-MCM-41 material with well-ordered pores and high surface areas but with a lower quantity of grafted 3-aminopropyltriethoxysilane than the indirect method. To remove the organic template in the indirect method, solvent extraction with HCl/C2H5OH and calcination at 500°C were used, and the former gave a higher quantity of grafted 3-aminopropyltriethoxysilane in the resulting aminopropyl-MCM-41 materials. The experimental data were applied to the isotherm models of adsorption including Langmuir, Freundlich, Redlich–Peterson, and Sips either in the linear or nonlinear form. In order to avoid the bias of the determination coefficient and the error function method, the paired-samples t-test as an alternative method was first proposed to look for the most appropriate adsorption isotherms. The maximum adsorption capacity of Cd(II) and Pb(II) was 14.08 mg·g−1 and 64.21 mg·g−1, respectively. The mechanism of complexation and isoelectric interaction was suggested to explain the adsorption of Pb(II) and Cd(II) from aqueous solutions on aminopropyl functionalised MCM-41 in the range of pH from 2 to 9.